Preaching and theology in Anglo-Saxon England: Aelfric and Wulfstan - Gatch, Milton McC. (Milton McCormick) (University of Toronto Press, 1977)
In Preaching and Theology in Anglo-Saxon England, Professor Gatch deals with two aspects of the writings of Ælfric and Wulfstan that have been hitherto ignored by scholars of the period.